Estrategia de marketing y publicidad en la Vulcanizadora y Lavadora Wachito de la cuidad de Babahoyo en el periodo 2022. - Cuello Ruiz, Kennia Suymey (2023)
The company "Lavadora y Vulcanizadora Wachito" in Babahoyo, with a decade of experience in oil changes, maintenance and sale of spare parts for vehicles and buses, faces a decrease in its income due to growing competition and lack of adaptation to modern strategies marketing, such as the use of social networks. The general objective of this study is to analyze the company's advertising and its weak points. Specific objectives include evaluating current advertising strategies, analyzing brand perception, and identifying areas for improvement in advertising strategies. The results reveal that current strategies focus on traditional media, limiting their reach and ability to measure impact. The "Wachito" brand fails to establish an effective connection with the target audience. Therefore, a transformation towards digital marketing strategies and an active presence on social networks is recommended. This includes creating profiles on platforms such as Facebook, Instagram and Twitter, along with investing in targeted online advertising. Furthermore, it is suggested to develop a strong and coherent brand identity to improve brand perception. To ensure the success of these strategies, it is proposed to establish clear monitoring and evaluation metrics, which will allow measuring the impact of the strategies, such as the increase in interaction on social networks and traffic to the website, and adjust them as necessary, the The company must adapt to new marketing and advertising trends to regain its competitiveness in the market.